CAR‐T cells derived from multiple myeloma patients at diagnosis have improved cytotoxic functions compared to those produced at relapse or following daratumumab treatment. Issue 3 (21st June 2022) - Abecassis, Audrey; Roders, Nathalie; Fayon, Maxime; Choisy, Caroline; Nelson, Elisabeth; Harel, Stephanie; Royer, Bruno; Villesuzanne, Camille; Talbot, Alexis; Garrick, David; Goodhardt, Michele; Fermand, Jean‐Paul; et al.
Abstract: Chimeric antigen receptor T cells (CAR‐T) have provided promising results in multiple myeloma (MM). However, many patients still relapse, pointing toward the need of improving this therapy. Here, we analyzed peripheral blood T cells from MM patients at different stages of the disease and investigated their phenotype and capacity to generate functional CAR‐T directed against CS1 or B Cell Maturation antigen. We found a decrease in naive T cells and elevated frequencies of exhaustion markers in T cells from treated MM patients. Interestingly, individuals treated with daratumumab display elevated ratios of central memory T cells. CAR‐T derived from patients at relapse show reduced in vitro expansion and cytotoxic capacities in response to MM cells compared to those produced at diagnosis. Of note, CAR‐T from daratumumab treated patients display intermediate defects. Reduced anti‐myeloma activity of CAR T cells from treated patients was also observed in a mouse model. Our findings suggest that T cell defects in MM patients, specifically during relapse, have a major impact on their capacity to generate efficient therapeutic CAR‐T. Selecting naive or central memory T cell subsets to generate therapeutic T cells could improve the CAR‐T therapy for MM.